2018
DOI: 10.1021/acsami.8b09878
|View full text |Cite
|
Sign up to set email alerts
|

Fast Switching Properties and Ion Diffusion Behavior of Polytriphenylamine Derivative with Pendent Ionic Liquid Unit

Abstract: A novel triphenylamine derivative-linked ionic liquid unit, 1-(6-((4-(bis(4-(thiophen-2-yl)phenyl)amino)benzoyl)oxy)hexyl)-3-methyl-imidazolium tetrafluoroborate (TTPACIL-BF), was designed and synthesized successfully, and its corresponding polymer PTTPACIL-BF was obtained by the electropolymerization method. The highest occupied molecular orbital energy band of TTPACIL-BF is higher and the onset oxidative potential lower compared with that of 6-bromohexyl 4-(bis(4-(thiophen-2-yl)phenyl)amino) benzoate (TTPACB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 29 publications
(37 reference statements)
1
16
0
Order By: Relevance
“…Table 4 shows the main ionic liquid structures discussed in this review. Through the chemical functionalization [137] Copyright 2018, American Chemical Society. b) Spectro-electrochemical cell configuration for the analysis of ECDs and the reduction-oxidation mechanism of the new smart PIL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 4 shows the main ionic liquid structures discussed in this review. Through the chemical functionalization [137] Copyright 2018, American Chemical Society. b) Spectro-electrochemical cell configuration for the analysis of ECDs and the reduction-oxidation mechanism of the new smart PIL.…”
Section: Discussionmentioning
confidence: 99%
“…The result indicated that the IL‐based electrolytes presented a faster electrochromic switching time than the traditional electrolytes without ILs unit, attributing to the improved ionic conductivity and ion diffusion coefficient with the introduction of ionic liquid segment as shown in Figure a. [ 137 ] The particular behavior further proved that the ion diffusion behavior played an important role in electrochromism and has a significant influence on its performance, especially the switching time. Besides, an all‐in‐one switchable electrochromic device with remarkably fast response time ( t red = 14 s; t ox = 17 s) and good coloration efficiency (76.8 cm 2 C −1 ) has been developed by integrating a viologen unit into the main chain of ILs.…”
Section: Il‐based Electro‐responsive Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ferrocene, triphenylamine, catenanes, pseudorotaxane, azobenzene, spiropyran, pyridines, diarylethene and phthalocyanines extensively investigated under light at various excitation wavelengths and applied into molecular machines, actuators, switches and electronic applications. [7][8][9][10][11][12] Whereas, tetrathiafulvalenes (TTFs), thiophenes, napthelenediimides (NDIs) and metalpolypyridyl complexes considered eletrochromic materials owing to mixed valence species generation via voltage leads artificial muscles, nanorobots and electronic noses. Likewise, extended diimides, porphyrins, tetrathiazolylthiophene, Schiff bases and borondipyrromethane moieties responded very well with sonication, force, stress/strain, heat and pH results the memory devices, drug-delivery and chemotherapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochromic (EC) materials as a new functional material have shown broad application prospects in smart windows, displays, and data storage devices . Conjugated polymers (CPs) have been used in EC devices as active layer, because of their fast switching time, high optical contrasts, flexible processability, and easy tunable color . For the realization of EC display devices, it is indispensable to obtain the neutral red, green, and blue (RGB) polymers for meeting the full‐color showing.…”
Section: Introductionmentioning
confidence: 99%